2006
DOI: 10.2807/esw.11.31.03015-en
|View full text |Cite
|
Sign up to set email alerts
|

Measles outbreak in Grosseto, central Italy, 2006

Abstract: From 2003 to 2007, Italy is implementing a national plan to eliminate measles and congenital rubella

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 0 publications
0
13
1
Order By: Relevance
“…In addition to supporting the recommendation of vaccination of health care workers, this event suggests that hospitalization should be reserved for serious cases, and home care should be encouraged during outbreaks. Pneumonia, a classic complication of measles, occurred in 2.1% of patients-a percentage similar to or even greater than that reported in studies from Germany [12] but lower than rates reported in other studies [16,30,34] and evidently very different from the figure of 26.5% reported by Van den Hof et al [36] from The Netherlands. The methodologies used to record complications during outbreaks are probably not homogenous and should accord international guidelines [22], because this information is important in evaluating the magnitude of the problem.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…In addition to supporting the recommendation of vaccination of health care workers, this event suggests that hospitalization should be reserved for serious cases, and home care should be encouraged during outbreaks. Pneumonia, a classic complication of measles, occurred in 2.1% of patients-a percentage similar to or even greater than that reported in studies from Germany [12] but lower than rates reported in other studies [16,30,34] and evidently very different from the figure of 26.5% reported by Van den Hof et al [36] from The Netherlands. The methodologies used to record complications during outbreaks are probably not homogenous and should accord international guidelines [22], because this information is important in evaluating the magnitude of the problem.…”
Section: Discussioncontrasting
confidence: 43%
“…Hospitalization of patients with measles probably has more to do with how cases are managed than with their severity; therefore, this may not be a good parameter for evaluating the magnitude and severity of an outbreak. In addition, there is a risk of nosocomial cases occurring both among patients visiting the hospital for other reasons and among health workers; this could increase disease transmission [16,30,34,35].…”
Section: Discussionmentioning
confidence: 98%
“…These sequences showed a maximum difference of 2 nucleotides (≤0.5%), difference that remained unchanged when the strains MVi/Kolar.IND/03.07/1 and MVs/London.GBR/25.07 were added to the alignment, while it showed an increase with the addition of the strain MVs/Grosseto.ITA/a301 [19]. …”
Section: Resultsmentioning
confidence: 99%
“…In France, the estimated number of measles cases dropped from 300,000 in 1985 to less than 10,400 cases in 2003 (3,48), and mortality has declined from 30 deaths per year in the 1980s to less than 10 per year in recent years (3,48). However, despite the success in controlling measles, the disease has not been eliminated in Europe; outbreaks still occur (2,3,13,18,29,34,35,45,48,50,52,53), and measles can still represent a serious health threat, especially in infants under 1 year of age (7,18).…”
mentioning
confidence: 99%